An Inventory of Problems–29 Sensitivity Study Investigating Feigning of Four Different Symptom Presentations Via Malingering Experimental Paradigm. Issue 4 (3rd July 2020) - Giromini, Luciano; Viglione, Donald J.; Pignolo, Claudia; Zennaro, Alessandro
Abstract: The Inventory of Problems–29 (IOP–29) is a newly developed, self-administered test designed to assist practitioners evaluating the credibility of various symptom presentations. In a recent simulation study comparing real patients against experimental feigners, its classification accuracy compared favorably with that of the Structured Inventory of Malingered Symptomatology and generalized better to different types of symptom reports (i.e., mood- or trauma-related vs. psychosis-related). Extending on these findings, this sensitivity study tested whether the IOP–29 would be similarly accurate in detecting feigning of conditions related to depression, mild traumatic brain injury, posttraumatic stress disorder (PTSD), and schizophrenia. Additionally, it also evaluated the susceptibility of the IOP–29 to uncooperative or random-like responding. Examination of 1, 200 IOP–29 records from 400 nonclinical Italian volunteers who took the Italian version of the IOP–29 3 times, in 3 different conditions (i.e., standard instructions, feigned disorder, and random-like responding), confirmed that the IOP–29 might be similarly valid across a wide variety of mental health and cognitive complaints. Indeed, using the standard a priori cutoff of the IOP–29 (i.e., ≥ .50), sensitivity estimates ranged from .86 (for feigned PTSD) to .95 (for feigned depression) and did not significantly differ from one symptom presentation to another. These findings were obtained despite the fact that participants were coached to respond in a believable manner. Interestingly, the random-like responding generated extremely variable IOP–29 scores.